"Uninformed" Consent: Patient Recollection From Surgical Consent in Hand Surgery—A Quality Improvement Initiative. (July 2021) - Yu, Monica; von Schroeder, Herbert P.
Background: Informed surgical consent is necessary and routine; however, it can have significant inadequacies. Our purpose was to investigate patient recollection of the surgical consent process and evaluate adequacy from the patient's perspective.Methods: A quality improvement framework was used. Two patient surveys capturing information recall and satisfaction of the consent process were administered in 5 consecutive hand clinics. All patients who previously underwent elective hand surgery were included.Results: There was exceptionally low recall of the risks and benefits of surgery in 103 consecutive patients who underwent hand surgery. Patients under age 35 had slightly better recall of surgical risks. Unexpected postoperative events affected patient perceptions of the consent process.Conclusions: Patients who have undergone elective hand surgery have poor recollection of the information discussed during the surgical consent process, and therefore the process is lacking. Surgeons may falsely assume that the consent process is sound because it is erroneously perceived as being sufficient by most patients.